Effect of Atypical Antipsychotic Medications on the Risk of Obstructive Sleep Apnea in Individuals With Schizophrenia - Habibolah Khazaie; Siamand Mazhar; Arash Parsa Moghadam; Mohammad Rasoul Ghadami; Sepideh Khazaie; Aliakbar Parvizifard (Sleep Medicine Research, 2022)
Background and Objective Weight gain and obesity could be side effects of taking atypical antipsychotic medications. They are major risk factors for obstructive sleep apnea. The purpose of this study was to investigate effects of atypical antipsychotic medications on the risk of obstructive sleep apnea in individuals with schizophrenia and control groups. Methods In this cross-sectional study, 123 patients with schizophrenia and 107 participants were selected from hospital staff and students using purposive sampling. Data were collected using structured clinical interview and Berlin questionnaires. Results Results showed that the risk of obstructive sleep apnea was significantly higher in individuals with schizophrenia. Age, body mass index, and phases of schizophrenia showed meaningful relationships with the duration of taking atypical antipsychotic medications with the risk of obstructive sleep apnea. However, the type of atypical antipsychotic medications did not have a significant relationship with the risk of obstructive sleep apnea. Conclusions Patients with schizophrenia treated with atypical antipsychotic medicationshave a higher risk of obstructive sleep apnea.